Pengembangan Media Permainan Tradisional Engklek ‘Opersia’ Tema Makanan Sehat Siswa Kelas V - Ardiyani, Yosi Tri; Kiswoyo, Kiswoyo; Ardiyanto, Asep (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
This study aims to determine the feasibility of developing a traditional engklek 'opersia' game with the theme of healthy food. The type of research used by the researcher is research and development. The data analysis technique used is descriptive qualitative. The instruments used are media validation assessment questionnaires, material validation, initial field trials. Data collection was obtained from the results of the media validation assessment and, material validation, initial field trials at SD Negeri 03 Majalang. The results of the first stage of media expert validation obtained an average validity of 86%, the second stage obtained an average validity value of 96% with a very feasible category. Material validation in the first stage obtained an average validity of 86.7%, the second stage obtained an average validity of 92.2% with the criteria very suitable to be used. In the initial field trial, the opera engklek media got a teacher response with media and material validation of 92% and 94.4%, respectively. In conclusion, the Opera Engklek media that has been developed is very valid and suitable for use in student learning at the fifth grade teacher of SD Negeri 03 Majalgu.